Change! Combining Analytic Approaches with Street Wisdom - Bammer, Gabriele (ANU Press, 2015)
Change happens all the time, so why is driving particular change generally so hard? Why are the outcomes often unpredictable? Are some types of change easier to achieve than others? Are some techniques for achieving change more effective than others? How can change that is already in train be stopped or deflected? Knowledge about change is fragmented and there is nowhere in the academic or practice worlds that provides comprehensive answers to these and other questions. Every discipline and practice area has only a partial view and there is not even a map of those different perspectives. The purpose of this book is to begin the task of developing a comprehensive approach to change by gathering a variety of viewpoints from the academic and practice worlds.